Corrigendum: The Remote Observatories of the Southeastern Association for Research in Astronomy (SARA). (24th June 2021) - Keel, William C.; Oswalt, Terry; Mack, Peter; Henson, Gary; Hillwig, Todd; Batcheldor, Daniel; Berrington, Robert; De Pree, Chris; Hartmann, Dieter; Leake, Martha; Licandro, Javier; Murphy, Brian; et al.
Abstract: Bill Gray of Project Pluto brought to our attention an error of 0.03° in the listed latitude of our Kitt Peak telescope. While correcting the table where this occurred, we also take the opportunity to update the instrument properties and weather statistics of our remote telescopes.